Glial Growth Factor 2 Regulates Glucose Transport in Healthy Cardiac Myocytes and During Myocardial Infarction via an Akt-Dependent Pathway - Shoop, Shanell; Maria, Zahra; Campolo, Allison; Rashdan, Nabil; Martin, Dominic; Lovern, Pamela; Lacombe, Véronique A. (Frontiers in Physiology, 2019)
Neuregulin, a paracrine factor in myocytes, promotes cardiac development via the ErbB receptors. Neuregulin-1β also improves cardiac function and cell survival after myocardial infarction, although the mechanisms underlying these cardioprotective effects are not well elucidated. Increased glucose uptake has been shown to be cardio-protective during myocardial infarction (MI). We hypothesized that treatment with a recombinant version of neuregulin-1β, glial growth factor 2 (GGF2), will enhance glucose transport in the healthy myocardium and during MI. Cardiac myocytes were isolated from MI and healthy adult rats, and subsequently incubated with or without insulin or GGF2. Glucose uptake was measured using a fluorescent D-glucose analog. The translocation of glucose transporter (GLUT) 4 to the cell surface, the rate-limiting step in glucose uptake, was measured using a photolabeled biotinylation assay in isolated myocytes. Similar to insulin, acute in vitro GGF2 treatment increased glucose uptake in healthy cardiac myocytes (by 40 and 49%, respectively, P=0.002). GGF2 treatment also increased GLUT4 translocation in healthy myocytes by 138% (P<0.01), while ErbB 2/4 receptor blockade (by afatinib) abolished these effects. In addition, GGF2 treatment enhanced Akt phosphorylation (at both threonine and serine sites, by 75% and 139%, respectively, P=0.029 and P=0.01), which was blunted by ErbB 2/4 receptor blockade. GGF2 treatment increased the phosphorylation of AS160 (an Akt effector) by 72% (P<0.05), as well as the phosphorylation of PDK-1 and PKC (by 206% and 100%, respectively, P<0.05). During MI, cardiac GLUT4 translocation was downregulated by 44% (P=0.004) and was partially rescued by both in vitro insulin and GGF2 treatment. Our data demonstrate that acute GGF2 treatment increased glucose transport in cardiac myocytes by activating the ErbB 2/4 receptors and subsequent key downstream effectors (i.e., PDK-1, Akt, AS160, and PKC). These findings highlight novel mechanisms of action of GGF2, which warrant further investigation in patients with heart failure.